Improving English Pronunciation Through Phonetics Instruction in Yemeni EFL Classrooms - Fadhl Mohammed Awadh Mohammed Awadh; Nur Hidayanto Pancoro Setyo Putro; Albert Efendi Pohan; Yasir Ayed Alsamiri (Journal of Languages and Language Teaching, 2024)
The context of English education in Yemen provides a critical backdrop for comprehending the challenges Yemeni students face in acquiring proficiency in English pronunciation. These challenges are primarily rooted in the distinct differences between the Arabic and English sound systems, variations in syllable structure and intonation, and the influence of local dialects. Such factors are instrumental in identifying the obstacles Yemeni learners encounter in accurately articulating English phonemes. This research delves into the efficacy of phonetics instruction, specifically phonics training, in ameliorating English pronunciation skills among students in English as a Foreign Language (EFL) settings in Yemen. Employing a literature review methodology, this study meticulously collects and analyzes data from pertinent academic sources to assess the impact of phonics training on pronunciation proficiency. The findings reveal a significant enhancement in students' ability to correctly identify and articulate English phonemes, thereby improving their verbal interaction and comprehension skills, and bolstering their confidence in English communication. The contributions of this study are manifold. It illuminates the pivotal role of phonetics instruction in refining English pronunciation among EFL learners in Yemen, providing empirical evidence to support the integration of phonetic teaching within the EFL curriculum. Moreover, it advocates for the enrichment of educational resources and teacher development programs, emphasizing the importance of prioritizing English pronunciation in Yemen's English language education framework. Through its insights, this study not only addresses a critical gap in the literature but also proposes actionable recommendations to enhance the effectiveness of English pronunciation teaching in Yemeni EFL classrooms. In essence, this study underscores the transformative potential of phonics training in elevating the English language proficiency of Yemeni students, thereby contributing significantly to the broader discourse on language acquisition and pedagogy.